Post-Biopsy Pneumothorax Incidence in Patients Treated with Biosentry Plug Device - Abouodah, Hythem; Werner, Gregg; Fahrbach, Thomas; Fox, Cameron; Mazurek, Jared; Lott, Jeremy; Walter, Carissa; Clark, Lauren; Custer, Brandon (Kansas Journal of Medicine, 2021)
Introduction: This study aimed to determine if Biosentry Plug Device (BP), a prophylactic sealant used to prevent pneumothorax after lung biopsies, reduced post-lung biopsy pneumothorax rates and other complications compared to no device utilization.Methods: This single institution, retrospective cohort study included patients who received a lung biopsy in the department of interventional radiology from May 1, 2015 to August 31, 2017. Data such as sex, race, ethnicity, COPD status, degree of lung bullae if present, smoking status, and use of BP were recorded. Decisions to use BP were based on operator preference. A chi squared analysis was used with a p value